The reasons for ceramic-on-ceramic revisions between the third- and fourth-generation bearings in total hip arthroplasty from multicentric registry data - Sang-Min Kim (Nature Portfolio, 2021)
Abstract This study aimed to evaluate (1) the overall reasons for first revision in CoC THAs; (2) whether the reasons for revision differ between third-generation and fourth-generation CoC THAs; and (3) the specific factors associated with bearing-related problems as the reason for revision. We retrospectively reviewed 2045 patients (2194 hips) who underwent first revision THA between 2004 and 2013, among which 146 hips with CoC bearings underwent revision. There were 92 hips with third-generation ceramic bearings and 54 hips with fourth-generation ceramic bearings. The major reasons for CoC THA revisions were ceramic fracture and loosening of the cup or stem. When ceramic fracture, squeaking, incorrect ceramic insertion, and unexplained pain were defined as directly related or potentially related to ceramic use, 28.8% (42/146) of CoC revisions were associated with bearing-related problems. Among the third-generation ceramic bearings, revision was performed in 41.3% (38/92) of cases owing to bearing-related problems whereas revisions were performed for only 7.4% (4/54) of cases with fourth-generation ceramic bearings owing to bearing-related problems (p < 0.001). Younger age, lower American Society of Anesthesiologists (ASA) grade, and preoperative diagnosis of osteonecrosis were factors related to CoC THA revisions due to bearing-related problems.